Pengaruh Pengembangan Karir, Kompensasi, dan Iklim Organisasi Terhadap Loyalitas Karyawan Alpha Hotel Pekanbaru - Fitri, Della Ayunda; ., Suryalena (Trunojoyo University of Madura, 2023)
The study aims to determine the effect of career development, compensation, and organizational climate on employee loyalty at Alpha Hotel Pekanbaru. In this study method used was quantitative descriptive analysis with the SPSS program. The population in this study were 50 employee Alpha Hotel Pekanbaru, with the sample technique used, namely cencus/total sampling. Data collection techniques through questionnaires. Types and sources of data using primary data and secondary data, measurement collection techniques using a Likert scale. The data analysis includes validity test, reliability test, normality test, multicolliniearity test, heteroscedasticity test, multiple linear regression analysis, coefficient of determination test, and significance test with t test (partial), and F test (simultaneous). The results of this study indicate that career development has a significant effect on employee loyalty. The second shows that compensation has a significant effect on employee loyalty. The third shows that organizational climate has a significant effect on employee loyalty. Th results of research on the effect of career development, compensation, and organizational climate on employee loyalty at Alpha Hotel Pekanbaru shows that there is a significant effect.